FINANCIAL FEASIBILITY STUDY OF A CHEMICAL ENHANCED OIL RECOVERY PROJECT IN INDONESIA BASED ON CONVENTIONAL DISCOUNTED CASH FLOW (DCF) AND REAL OPTION VALUATION MODEL: CASE STUDY AT PT. PERTAMA - Taskia Amin, Junita
In 1962, Indonesia became a member of the Organization of the Petroleum Exporting Countries (OPEC), which is an organization that regulates the production, supplies, and prices of petroleum on the international market. Indonesia had become an oil exporter that was known throughout the world for a number of years prior to this. However, oil production in Indonesia has been steadily declining for years. One of the reasons for this trend is that there has not been enough money invested in the exploration of new oil wells in Indonesia; as a result, the majority of upstream oil and gas work in Indonesia is focused on the exploitation of older wells, the output of which will naturally continue to fall over time. As a direct consequence of this, Indonesia turned into a country that was dependent on net oil imports in the year 2003. As a result, extra operations are required in order to optimize the amount of oil output that can be obtained from these existing wells. One of these additional procedures is known as chemical enhanced oil recovery (CEOR). The primary goal of EOR in and of itself is to mobilize the residual oil by improving the efficiency of oil displacement and volumetric sweep. The government has assigned PT. PERTAMA, a subsidiary of PT. XYZ (a state-owned company operating under the supervision of SKK Migas and PT Pertamina) that is active in the upstream sector in Indonesia to carry out one of the CEOR projects that have been determined by the government. PT. PERTAMA is engaged in the upstream sector in Indonesia. The purpose of this study is to investigate the financial feasibility study of the CEOR Project using a Conventional Discounted Cash Flow (DCF) and Real Option Valuation (ROV) Model. Discounted Cash flow is a valuation method that estimates the value of an investment using its expected future cash flow without consider any future uncertainties, while Real Option Valuation Model is a valuation method that adopt uncertainties and flexibilities to the project such as deferring, abandoning, expanding, staging, or contracting a capital investment project. The gross split technique – a scheme in which the calculation of profit sharing for the management of oil and gas work areas between the Government and Oil and Gas Contractors is calculated in advance - is the revenue-sharing policy that was utilized for the purpose of the project economic computation. According to the findings of the economic analysis that was conducted using the DCF technique, it is determined that the project cannot be carried out economically because the net present value (NPV) reveals a loss of 2,911 million USD. However, by incorporating a strategic option, such as an option to postpone and time flexibility into the project, the actual option valuation model was able to contribute to an increase in the value that brought it up to 11,416 MUSD. As a consequence of this, it is possible that the project will be financially viable if the operation is postponed until the following year if the price of oil is higher than 85.2 USD per barrel.